Knowledge monopoly and policy change: EU-backed VET reforms in Azerbaijan - Majid Bayramli (International Journal for Research in Vocational Education and Training (IJRVET), 2026)
Context: Azerbaijan's vocational education and training (VET) system has undergone a significant reform, culminating in the enactment of the Law on Vocational Education in 2018. Despite not being a member of the European Union (EU) and lacking formal political, economic, or cultural alignment with the union, Azerbaijani policymakers adopted EU-backed policy solutions in designing the country's new VET system. This raises important questions about the motivations behind this policy shift and the factors that shaped it, especially given the limited formal influence of the EU in non-member states.~ Approach: This study applies a Cultural Political Economy (CPE) framework to examine the adoption of EU policy ideas in Azerbaijan's VET reforms. The research focuses on the policy transfer process, tracing how EU-driven concepts were introduced, negotiated, and institutionalized within Azerbaijan's education system. It explores the role of international organizations, domestic political actors, and political agenda in shaping policy decisions. The analysis draws on a qualitative case study approach, using document review and interviews with key national stakeholders to explore how decisions were shaped. It pays close attention to the interplay of ideational and material factors that influenced the design and content of the 2018 law.~ Findings: The findings show that, even in differing political and economic contexts, education sectors can independently shape policy directions. In the case of Azerbaijan, policymakers turned to EU VET models not as a result of direct pressure, but as a response to pressing domestic challenges. This engagement was not a simple replication of EU practices, but a selective and negotiated process shaped by the interaction between international frameworks and national institutional conditions. A key factor in this process was the EU's role as a provider of technical expertise and policy knowledge. Although the EU did not impose specific reforms, its control over policy-relevant knowledge and technical expertise structured the reform space, guiding Azerbaijani decision-makers toward particular options while limiting the visibility of alternatives.~ Conclusion: This study contributes to the understanding of policy transfer in non-EU contexts, emphasizing the role of external knowledge provision in shaping national reforms beyond direct political or economic leverage. The findings underscore the subtle but powerful ways international organizations influence education policy, even in the absence of formal conditionality agreements.
Keywords: 330; Vocational Education and Training; VET; Policy Transfer; Europeanisation; Knowledge Governance; VET Reform